Pendeteksian Keberadaan Struktur Sesar pada Batuan Vulkanik dengan Metode Magnetik - Suntoko, Hadi; Nurdin, Muhammad; Susilo, Yarianto Sugeng Budi; Hamzah, Imam (EKSPLORIUM, 2012)
Banten NPP site is located in Kramatwatu-Bojonegara district, Serang, it has a surface fault indication in volcanic rock it known that to Northwest-Southeast trending. Indications of the satellite imagery analysis maps confirm the straightness (lineament) at Bojonegara-1 fault. A lineament as fault structures to be necessary to prove existence of magnetic method in order to determine the continuity of Bojonegara-1 fault in the subsurface. The purpose of the study is to know the Bojonegara fault in the subsurface. Through on interpretation and analysis of the earth's magnetic field on the scale of an object to be caused a variety of sources it can be detected by intensity magnetic as a total magnetic moment of unity volume to study the condition of the deformed rocks. The study used are G856-AX Proton Magnetometer precession magnetometer (PPM) over a stretch of 300 m and 10 m intervals for the fault lineament. The measurement system uses two sensors and observations, corrected magnetic field strength is ideal as a reference for the total magnetic field anomalies. Preliminary results show that the fault lineament is indicated at the observation point with a depth to unknown so that it still need more detailed. Magnetic method is very good for an early review of fault structures with fast and simple.